(TRANS)GENDER SHADES. THE DANGERS OF ARTIFICIAL INTELLIGENCE FOR THE RIGHT TO IDENTITY FOR TRANSGENDER PEOPLE (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This contribution evaluates the impact of artificial intelligence (AI) on transgender rights, focusing on gender identity protection. While society tries to acknowledge gender complexity, AI operates with biased binary models, marginalizing transgender people. AI’s foundation often misinterprets gender as a fixed, physiological binary, excluding transgender input. This disparity between AI construction and individual gender identity rights presents constitutional issues.
Keywords: Artificial Intelligence (AI); Discriminatory Algorithms; Transgender People’s Rights; Right to Gender Identity; Constitutional Challenges